1997
DOI: 10.1176/ajp.154.3.322
|View full text |Cite
|
Sign up to set email alerts
|

Religion, psychopathology, and substance use and abuse; a multimeasure, genetic-epidemiologic study

Abstract: Objective: The authors sought to 1) understand the sources of familial resemblance for religiosity, 2) 1997; 154:322-329)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
1
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(85 citation statements)
references
References 55 publications
7
76
1
1
Order By: Relevance
“…It is also possible that the time order between religious involvement and alcohol problems is reversed; some subjects may increase or decrease their religious involvement as a result of having problems with alcohol. Kendler et al's (1997) study suggested that these alternative relationships are less likely, reporting a stronger relationship between earlier church attendance and later alcohol use rather than between earlier alcohol use and later attendance.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…It is also possible that the time order between religious involvement and alcohol problems is reversed; some subjects may increase or decrease their religious involvement as a result of having problems with alcohol. Kendler et al's (1997) study suggested that these alternative relationships are less likely, reporting a stronger relationship between earlier church attendance and later alcohol use rather than between earlier alcohol use and later attendance.…”
Section: Discussionmentioning
confidence: 91%
“…However, prospective studies are needed to help clarify the relationships between religious involvement, ADH gene variants, and drinking and alcohol dependence symptoms because the current study is cross-sectional and religious involvement was measured at a single time point. Religious services attendance in the past 12 months before interview may not be representative of lifetime attendance, although there is some evidence that services attendance is relatively stable over time (Kendler et al, 1997;Koenig & Vaillant, 2009). Some studies identify reductions in religious attendance from adolescence to young adulthood (Button et al, 2011), which may be less relevant to this adult sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Underlying mechanism which is used to explain this relationship is the buffering hypothesis; religiosity may buffer the impact of distress on psychological wellbeing and physiological health (Kendler, Gardner, & Prescott, 1997;Krause, 1998;Pargament, 1997).…”
Section: Introductionmentioning
confidence: 99%